BAHAGIA PERSPEKTIF SYED MUHAMMAD NAQUIB AL-ATTAS - Jarman Arroisi; Novita Sari (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
In facing life and life, the problem that mankind always feels is the two choices between happiness and misery. A person who always thinks acts, and behaves positively can certainly achieve positive results and get a sense of happiness. However, not a few people behave and behave negatively expecting positive results and wish to achieve a sense of happiness. Instantaneous motivational trends like these are evidence that between reality and hope is often not linear. This text aims to explore the happy ideas of Naquib al-Attas's perspective. By using the analytical descriptive method, this study found several important conclusions. First, al-Attas divides the happy aspect into two types, namely the aspect of physical and spiritual happiness. Second, for al-Attas, the highest level of happiness is the level of someone who knows himself or makrifatullah. Third, this highest happiness according to al-Attas cannot possibly be achieved by people who always emphasize the material aspects of their life, without knowing themselves, as is the case in modern-secular Western societies.